2022
DOI: 10.1097/hnp.0000000000000514
|View full text |Cite
|
Sign up to set email alerts
|

Classical Massage and Relaxation Exercise on Symptom Status and Quality of Life in Advanced Stage Patients With Heart Failure

Abstract: This randomized controlled study aimed to investigate the effects of classical massage (CM) and Benson relaxation exercise (BRE) on symptom status and quality of life (QoL) in patients with heart failure (HF). Seventy-two patients with HF were recruited from 4 hospitals in Ankara, Turkey. The study sample was allocated to a CM (n = 24), BRE (n = 26), or control group (n = 22) based on the New York Heart Association classification of HF (stages III and IV) through stratified randomization. The intervention grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
(111 reference statements)
1
7
0
Order By: Relevance
“…While evaluating the findings of the study, studies examining the effect of foot massage applied to different patient groups on peripheral edema were used. Similar to the results obtained from our study in the literature, Gülbahar and Gok Metin13 stated that 14 sessions of foot-hand massage applied to patients with heart failure had positive effects on heart failure symptoms such as edema, dyspnea, and pain. In one of the studies examining the physiological edema effect of foot massage in pregnant women, foot massage has been suggested to be an effective and easy method to reduce foot edema 18.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…While evaluating the findings of the study, studies examining the effect of foot massage applied to different patient groups on peripheral edema were used. Similar to the results obtained from our study in the literature, Gülbahar and Gok Metin13 stated that 14 sessions of foot-hand massage applied to patients with heart failure had positive effects on heart failure symptoms such as edema, dyspnea, and pain. In one of the studies examining the physiological edema effect of foot massage in pregnant women, foot massage has been suggested to be an effective and easy method to reduce foot edema 18.…”
Section: Discussionsupporting
confidence: 91%
“…In a study conducted by Gülbahar and Gok Metin,13 hand-foot massage and body relaxation stretching movements were applied to patients with CHF stages III and IV twice a day for 7 days. In the evaluation of the first and seventh days of the study, it was found that the symptom states (dyspnea, fatigue, sleep) were found to be significantly alleviated 13…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations